ACHIEVING DIVERSITY THROUGH ONLINE INTER-INSTITUTIONAL COLLABORATIONS - McCurdy, Shari (Online Learning, 2006)
This paper examines best practices for technology use in online, collaborations between the University of Illinois at Springfield and Chicago State University in class sessions shared across institutional boundaries. We explore the collaborations between these two ethnically and culturally diverse institutions. The University of Illinois at Springfield received two grants in the fall of 2004 to address the challenge of encouraging diversity in online and on campus classes. One grant, from the Illinois Board of Higher Education supported the development of online collaborations between classes at UIS with a student population that is approximately 9% ethnic minority and Chicago State University with a student population that is more than 90% ethnic. Highlighted are synchronous and asynchronous exchanges using Elluminate Live’s synchronous, web-based two–way audio conferencing and Blackboard’s asynchronous discussion board technologies.